Inklusivitas Misi Yesus dalam Mukjizat Pemberian Makan: Analisis Sosio-Redaksional atas Markus 8:1-10 (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2025)
The story of the miracle of the multiplication of the loaves in Mark 8:1-10 duplicates Mark 6:30-44, with several significant differences to highlight certain theological and social messages to Mark's community. The differences between the two stories include the geographical context, the audience's character, the symbolism of numbers, and the number of people fed. By examining the differences in Mark 8:1-10 and 6:30-44, this study aims to reveal the theological and social meanings contained in the story of the feeding of the four thousand. The method used is socio-editorial, which combines editorial criticism with social analysis. The results of the study show that the elements of difference in the narrative, such as the geographical context, the characteristics of the audience, the symbolism of the seven loaves, seven baskets, and the number of four thousand people, explicitly emphasize the inclusiveness of Jesus' mission and challenge the boundaries of exclusivity based on ethnicity, social status, and religious identity in Jewish society at that time.
Keywords: inklusivitas misi yesus; mujizat pemberian makan; Markus 8:1-10